Family coping with mental illness - Ana García Laborda; Carlos Rodríguez Rodríguez (Universidad de Alicante, 2012)
Mental illness has both personal and family implications. Coping strategies and behaviours towards disease can change according to resources used. Amongst the resources, the main factor is the family, thus the relevance of the family support network for the management of the person with mental health problems.